Emergence, persistence, and positive selection of yellow fever virus in Colombia - Perez, Lester J.; Perez-Restrepo, Laura S.; Ciuoderis, Karl; Usuga, Jaime; Moreno, Isabel; Vargas, Vanessa; Arévalo-Arbelaez, Angela J.; Berg, Michael G.; Cloherty, Gavin A.; Hernández-Ortiz, Juan Pablo; Osorio, Jorge E. (Frontiers in Microbiology, 2025)
Yellow fever virus (YFV) is an arbovirus that causes acute febrile illness (AFI), in tropical areas of South America and Africa. Through a 2020–2023 AFI study in Leticia, Colombia, leveraging metagenomic next-generation sequencing (mNGS), we identified and isolated YFV (LET1450). Phylogenetic analysis showed this strain belongs to South American genotype II (SamII), linked to Peruvian and Bolivian sequences emerging around 1989. Phylodynamic analysis indicates these strains, with a unique genetic makeup, could have reduced vaccine susceptibility, and due to positive Darwinian selection have an enhanced adaptive capacity. Antigenic analysis identified additional immune-evasive traits and this strain’s potential for wider Latin American spread. Phylogeographic reconstruction demonstrated the persistence of YFV in Colombia is not due to repeated external introductions, but results from continuous, cryptic internal circulation. This study highlights the crucial role of mNGS in monitoring emerging strains and underscores the need for genomic surveillance of YFV and other arboviral infections.